Understanding the molecular mechanisms of the differences in the efficiency and stability of all-polymer solar cells. Issue 5 (18th January 2022) - Wu, Qiang; Wang, Wei; Chen, Zeng; Xia, Xinxin; Gao, Mengyuan; Shen, Hao; Zhu, Haiming; Lu, Xinhui; Ye, Long; Xia, Jianlong; Min, Jie
Abstract : This work provides an in-depth insight into the rational selection of the P D s– P A s pair and fine-tuning of the active layer morphology, which is conducive to understanding the miscibility–morphology–function relations. Abstract : In spite of the great success of all-polymer solar cells (all-PSCs) in terms of device efficiency mainly owing to the vigorous development of polymer donors ( P D s) and polymer acceptors ( P A s), the synergistic effects of the molecular structure and molecular weight ( M w ) of P D and P A materials as well as P D – P A pair miscibility on device performance are still unclear and rarely reported. Herein, we introduced PBDB-T and its congener materials (PM6 and PM7) as P D s with comparable M w s and two PYT batches as P A s with different M w s (PYT-M and PYT-H) to deeply investigate the effects of molecular mechanisms on the device efficiency and stability in these six systems. Benefiting from proper P D – P A miscibility owing to the matched molecular structure and M w s, both PBDB-T:PYT-H and PM6:PYT-M systems with suitable phase separation show comparable device efficiencies, which are much better than those of the other four all-polymer systems. Impressively, further investigation demonstrates that the PBDB-T:PYT-H active layer is more stable than the PM6:PYT-M one, resulting from the trade-offs between molecular miscibility and M w . This work not only employs the synergetic effect of the molecular structure and molecular weight on device efficiency and stability but also provides a promising strategy to simultaneously improve the device performance of all-PSCs.